2013
DOI: 10.1136/vetreccr.d4635rep
|View full text |Cite
|
Sign up to set email alerts
|

Review of seven cases of granulosa cell tumour of the equine ovary

Abstract: This paper reviews the equine granulosa cell tumour (GCT) and describes the clinicopathological features, treatment and outcome in seven cases of GCT in mares. Mares were presented with unilateral ovarian enlargement during the 2007 to 2010 breeding seasons. The mean (sd) age of the mares was 11.7 (5.96) years. Three mares were multiparous barren, three were nulliparous and one was primigravida. Behaviour at presentation was 57 per cent anoestrus, 28 per cent with stallion-like behaviour and 14 per cent with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…The granulosa tumour population can be observed with multiple cystic appearances, comprising layers of polygonal epithelial cells with moderate eosinophilic cytoplasm, similarly reported by Crabtree (Crabtree, ). The tumour aspects are also detailed as macro‐ or micro‐follicular, with trabeculae and tubules, but the expression pattern of the immunohistochemistry markers (cytokeratin, α‐actin, vimentin, α‐inhibin, desmin and c‐erbB‐2 oncoprotein) in Graafian and tertiary follicles were similar to the normal ovary.…”
Section: Discussionsupporting
confidence: 71%
“…The granulosa tumour population can be observed with multiple cystic appearances, comprising layers of polygonal epithelial cells with moderate eosinophilic cytoplasm, similarly reported by Crabtree (Crabtree, ). The tumour aspects are also detailed as macro‐ or micro‐follicular, with trabeculae and tubules, but the expression pattern of the immunohistochemistry markers (cytokeratin, α‐actin, vimentin, α‐inhibin, desmin and c‐erbB‐2 oncoprotein) in Graafian and tertiary follicles were similar to the normal ovary.…”
Section: Discussionsupporting
confidence: 71%
“…Tumors which invade the theca cells in the ovary lead to an increase in the secretion of testosterone (Ball et al, 2013). Excessive testosterone results in a changing of behavior into stallion-like behavior that is one of the typical symptoms in mares with GTCT (Stabenfeldt et al, 1979;Bosu et al, 1982;Crabtree, 2011). In this study 12 out of 13 mares showed stallion-like behavior symptoms due to GTCT.…”
Section: Resultsmentioning
confidence: 60%
“…Mares were found affected from age 4-18 years old. Some researchers found that GTCT can occur in horses with an average age of 11.7 years old (Crabtree, 2011) and between age 2-20 years old (Meagher et al, 1977). In this study, one mare went through ovariectomy to remove tumors.…”
Section: Resultsmentioning
confidence: 99%
“…9 Initially, the sexual behaviour of affected mares is altered, and at a later stage acyclic, 6,10 often accompanied by elevated serum testosterone levels and stallion-like behaviour (typically in GTCT cases). 11,12 Support of diagnosis is generally made by laboratory analysis of serum levels of testosterone, progesterone, oestradiol, ir-inhibin, and Anti-Müllerian hormone (AMH). 6,13 The latter has recently gained importance because it is a sensitive parameter that becomes elevated in the initial stage of tumour growth.…”
Section: Introductionmentioning
confidence: 99%